Association between butchers and cancer mortality and incidence: A systematic review and meta-analysis. Issue 39 (September 2017) - Guo, Zhen-Lang; Wang, Jun-Yue; Li, Yu-Si; Gong, Lei-Liang; Gan, Shu; Wang, Shu-Sheng
Abstract: Background: In this study, we evaluated whether increased risks of mortality and cancer incidence exist among butchers worldwide. To achieve this goal, we conducted a systematic review and meta-analysis to investigate the correlations of the risks of cancer death and incidence with male and female butchers. Methods: We obtained data by performing a comprehensive literature search in several databases for eligible studies published before March 2017. Multivariable-adjusted standardized mortality ratios (SMRs) and odds ratio (OR), as well as associated 95% confidence intervals (CIs) and those by subgroups, were extracted and pooled. Results: A total of 17 observational studies comprising 397, 726 participants were included in the meta-analysis. The butcher occupation was not associated with all-cancer mortality risk, with pooled overall SMRs of 1.07 (95% CI 0.96–1.20). However, the pooled ORs revealed that butchers hold an elevated risk of total cancer incidence (OR, 1.51; 95% CI, 1.33–1.73). No proof of publication bias was obtained, and the findings were consistent in the subgroup analyses. Conclusion: Our results suggest that working as butchers did not significantly influence all-cancer mortality risk but significantly contributed to elevated all-cancer incidence risk. Nevertheless, well-designed observational studies on this topic are necessary to confirm and update our findings.